Ghana Work Program (FY15) : Poverty and Inequality Profile - World Bank (Washington, DC, 2015)
Since 1991 the national poverty rate of Ghana has more than halved. The estimated national headcount poverty ratio fell by 31.2 percentage points from 52.6 percent in 1991 to 21.41 percent in 2012. Heterogeneity of poverty outcomes is, however, high both across urban and rural areas and across regions. The robustness of these poverty trends is checked with trends of five correlates: urbanization and rural-urban migration, remittances, asset growth, labor market transformations, and agricultural productivity growth. Urbanization turns out to be highly correlated with poverty reduction. Poverty trends and asset index trends turn out to follow a similar pattern in both urban and rural areas and by regions: asset index increase where poverty decreases. In the report the authors try to understand the drivers of recent decrease in poverty in northern regions. The attention is focused on two different aspects, the agricultural productivity growth and the inflation patterns. In northern regions, there is a generalized increase in production of main food crops and an increase in productivity. To test the contribution of most of these drivers to poverty reduction, the authors estimated unconditional quintile regressions over the 20th, 40th, and 60th percentiles and decomposed the results using the Oaxaca Blinder method. To further strengthen the spatial analysis of poverty the authors constructed a new poverty map based on sixth Ghana living standard survey (GLSS 6) (conducted in 2012-13) in combination with the 2010 census, which was then compared with the 2000 map. This profile focuses on inequalities seen from three different perspectives: consumption inequality, inequalities of opportunities, and polarization.